Analysis of Electronic Word of Mouth and Green Product on Purchase Decision Mediated by Brand Image on Chery Omoda E5 Electric Car in Yogyakarta - Lahura, Armando; Lukitaningsih, Ambar; Fadhilah, Muinah (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the effect of Electronic Word of Mouth and Green Product on Purchase Decision of Chery Omoda E5 electric cars in Yogyakarta, with Brand Image as a mediating variable. Data from 37 respondents were collected via purposive sampling and analyzed using SmartPLS 4. Results show that e-WOM and Green Product do not directly influence Purchase Decision but positively affect Brand Image. Brand Image significantly mediates the effect of Green Product on Purchase Decision, but not the effect of Electronic Word of Mouth